2019
DOI: 10.1002/jnm.2545
|View full text |Cite
|
Sign up to set email alerts
|

An approach to determine cutoff frequency and maximum oscillation frequency of common emitter heterojunction bipolar transistor

Abstract: Analytical expressions for the short-circuit current gain and unilateral power gain of common emitter heterojunction bipolar transistor (HBT) are presented in this paper. These expressions are derived from a simplified π-type small signal equivalent circuit model, which takes into account the influence of the extrinsic resistances and base-collector capacitance distributed nature. Good agreement is obtained between measured and calculated results for both two indium phosphide (InP) HBT devices and a gallium ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The intrinsic elements will be used later in sensitivity analysis with measured S‐parameters. The hybrid− π small‐signal equivalent circuit model after de‐embedding is shown in Figure 1, [ 1 ] where R bi and R π is the intrinsic base resistance and base‐emitter resistance, respectively. C π is the intrinsic base‐emitter capacitance and g m is trans‐conductance [ 6 ] .…”
Section: Equivalent Circuit Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The intrinsic elements will be used later in sensitivity analysis with measured S‐parameters. The hybrid− π small‐signal equivalent circuit model after de‐embedding is shown in Figure 1, [ 1 ] where R bi and R π is the intrinsic base resistance and base‐emitter resistance, respectively. C π is the intrinsic base‐emitter capacitance and g m is trans‐conductance [ 6 ] .…”
Section: Equivalent Circuit Modelmentioning
confidence: 99%
“…Semiconductor devices are the basis of electronic industry, and microwave and millimeter‐wave devices have become the forefront of the development of electronic technology [ 1 ] . In the fields of satellite, wireless communication, automobile radar and production automation [ 2 ] , the requirements of frequency band are gradually increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al presented a review on the compact modeling of InP HBTs for THz integrated circuits. Useful improvements made for HBTs are reported on the analysis of intrinsic base resistances by Chen et al, on large‐signal models by Hu et al, on the determination of cutoff and maximum oscillation frequencies by Zhang and Gao, and on the thermal resistance calculation by Wang et al Due to a high breakthrough voltage and saturation velocity, GaN HEMTs is very promising for millimeter‐wave solid‐state power amplifiers. Chen et al reported an improved quasi‐physics zone division large‐signal model to account for electro‐thermal effects, which is valid for the ambient temperature range of 245 to 390 K. Physical parameters' effects, reliable parameter extraction, and dynamic thermal impedance extraction for the equivalent circuit models of GaN HEMTs are discussed by Mi et al, Chen et al, and Wang et al, respectively.…”
mentioning
confidence: 99%